The quero and the aryballos: a complementary reading - Cortijo Molina, Álvaro (2023)
Featured by the use of geometric designs, schematic figurative representations, and the importance of composition over pictorial details (Cummins, 2018), the Inca art had the role of diffusion of a power discourse and legitimation of the ruler regimen (Herring, 2021; Bray, 2000 and, Moseley, 1992). This paper, through the observation of Inca quero (qquero, wooden glass) and aryballos (urpu) of Cuzco Polychrome A and B style, with the revision of colonial documents and archaeological information, proposes an iconographic approximation about the concentric square carved motifs on the Inca queros. Read complementarily with the rhombus and phytomorphic motifs painted on the aryballos, the squares refer to the caves (also called “windows”) of Sutictocco and Marastocco, men- tioned in the Inca origin myths with the Tamboctocco’s cave and, by extension, to the subjects and allies of the Inca, being part of a message of legitimation through the theme of the mythic origin.